2018
DOI: 10.1155/2018/2450939
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Ban in Psychiatric Inpatient Unit: An Iranian Study on the Views and Attitudes of the Mental Health Staff and Psychiatric Patients

Abstract: Although the move to smoke-free mental health inpatient settings is an internationally common and popular trend, these policies are neither implemented nor supported by any national program in Iran. This study investigates the attitude of mental health staff and psychiatric patients toward smoking cessation in 2 psychiatric inpatient units (psychosomatic and adult general psychiatry) in the Taleghani general hospital in Tehran. One hundred and twenty participants of this cross-sectional study consist of 30 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(35 reference statements)
0
8
0
5
Order By: Relevance
“…This result can be an important motivator for healthcare professionals to support antismoking policy in mental health services. A study conducted in Iran found that 89% of healthcare professionals surveyed worry about their health because of their exposure to secondhand smoke 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be an important motivator for healthcare professionals to support antismoking policy in mental health services. A study conducted in Iran found that 89% of healthcare professionals surveyed worry about their health because of their exposure to secondhand smoke 25…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Iran found that 89% of healthcare professionals surveyed worry about their health because of their exposure to secondhand smoke. 25 Nursing professionals working the day shift and those on the private psychiatric ward were less supportive of smoking bans. No study was found in the scientific literature that compared opinions regarding the smoking bans in public and private mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…12.546/2011, which prohibits smoking in collective environments (public and private), is a challenge for mental health services, especially psychiatric hospitals, which have a higher prevalence of smokers and treat people with more severe tobacco dependence. In addition, the culture of smoking (using cigarettes as currency), inherited from asylums, is still common in these places (4)(5) .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is still resistance to smoking bans in mental health services. Recent studies carried out in Iran and Italy show that professionals are skeptical about the successful implementation of a smoke-free policy in these places (5)(6) . A Brazilian study revealed that the fear that the ban could affect hospital indicators, reducing the number of admissions and increasing discharge on request, for example, is one of the reasons for resistance in psychiatric hospitals, especially in private and philanthropic institutions (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Although many Western countries, including Australia, UK, Canada and the USA, have implemented smoking bans in inpatient psychiatric units, this is not the case throughout the world (Lawn & Campion, 2013). For example, recent publications document smoking being permitted in most mental health units in Iran (Beyraghi et al, 2018) and in the psychiatric hospital in Bahrain (Hamadeh et al, 2016). This is despite studies from the Middle East reporting a high prevalence of nicotine addiction among mentally ill people (Al Risi et al, 2018; Al‐Habeeb & Qureshi, 2000; Elkholy et al, 2018; Hamadeh et al, 2016; Milani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%